DEVELOPMENT OF ECONOMY MICROLEARNING MEDIA ASSISTED BY INSTAGRAM TO IMPROVE STUDENT LEARNING OUTCOMES - Anjarwati, Michella Audry; Dewi, Retno Mustika (Universitas Muhammadiyah Surakarta, 2025)
This study aims to develop and evaluate, describe how the feasibility, effectiveness, results of student’s responses to Instagram-assisted microlearning media to improve student learning outcomes. The resulting product is concist of content text, images, and videos share through in account @easyconomi. The uniqueness of this research lies in the use of Instagram as the primary medium for delivering microlearning materials, which has not been systematically utilized in the senior high school in Surabaya especially in economic subject. This research used Reaserch and Development (R&D) method with ADDIE model and was conducted at SMA Labschool UNESA 1 Surabaya, with 20 students. The methods of data collection are observation, quesionnaries, surveys and documentation. Data were collected through expert validation sheets, student response questionnaires than pre-test and post-test instrument and was analyzed with SPSS application using t-test and N-Gain test. It is recommended that this Instagram-assisted microlearning media be used alternative learning tool. The limitation of this reaserch lies in the small sample size and limited implementation duration. Future reaserch must involve more divrse participant and evaluate long-term impacts accros various subjects or school levels.